Steel
A steel material with a tailored chemical composition and microstructure, including MnS and MnTi composite sulfides, addresses the challenge of sulfuric acid dew point corrosion in boiler air preheaters, achieving superior corrosion resistance in high temperature, high concentration sulfuric acid environments.
Patent Information
- Application Number
- JP2021171177
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-10-19
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2041-10-19
AI Technical Summary
Steel materials used in boiler air preheaters face significant corrosion challenges in sulfuric acid dew point corrosion environments above 100°C, where high concentrations of sulfuric acid are present, requiring enhanced corrosion resistance at high temperatures.
A steel material with a specific chemical composition and microstructure, including MnS and MnTi composite sulfides, is developed to improve corrosion resistance. The composition ranges from 0.010% to 0.20% C, 0.04% to 1.00% Si, 0.20% to 2.00% Mn, and includes Cu, Cr, Ti, Ni, and other elements, with a ratio of (Si+Al+Ca)/Ti between 3.6 and 27.0, and a specific inclusion density and distribution.
The steel material exhibits excellent corrosion resistance in high temperature and high concentration sulfuric acid environments, with improved resistance to sulfuric acid dew point corrosion, as demonstrated by sulfuric acid immersion tests and tensile tests.
Smart Images

Figure 0007662941000001 
Figure 0007662941000002 
Figure 0007662941000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a steel material. [Background technology]
[0002] Boiler furnaces and incinerators at waste incineration facilities generate exhaust gases that contain water vapor, sulfur oxides, hydrogen chloride, etc. When this exhaust gas is cooled in the exhaust gas chimney, etc., it condenses into sulfuric acid and hydrochloric acid, which causes severe corrosion of the steel materials that make up the exhaust gas passage, a phenomenon known as sulfuric acid dew-point corrosion and hydrochloric acid dew-point corrosion.
[0003] To address these problems, sulfuric acid / hydrochloric acid dew-point corrosion resistant steels and highly corrosion resistant stainless steels have been proposed. For example, Patent Documents 1 to 4 propose steel materials with excellent sulfuric acid dew-point corrosion resistance to which Cu, Sb, Co, Cr, etc. have been added. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2001-164335 A [Patent Document 2] JP 2003-213367 A [Patent Document 3] JP 2007-239094 A [Patent Document 4] JP 2012-57221 A Summary of the Invention [Problem to be solved by the invention]
[0005] Steel materials containing Cu, Sb, Cr, etc. exhibit excellent corrosion resistance in sulfuric acid corrosive environments such as exhaust gas chimneys. However, steel materials used in boiler air preheaters and the like may be used in sulfuric acid dew-point corrosive environments exceeding 100°C. Furthermore, in such sulfuric acid dew-point corrosive environments exceeding 100°C, extremely high-concentration sulfuric acid exceeding 70% may be generated, and the steel materials used are required to have excellent corrosion resistance against high-temperature and high-concentration sulfuric acid.
[0006] An object of the present invention is to solve the above problems and to provide a steel material having excellent corrosion resistance in a high-temperature and high-concentration sulfuric acid corrosive environment. [Means for solving the problem]
[0007] The present invention has been made to solve the above problems, and the gist of the present invention is the following steel material.
[0008] (1) Chemical composition, in mass%, C: 0.010-0.20%, Si: 0.04 to 1.00%, Mn: 0.20-2.00%, Cu: 0.10-1.00%, Al: 0.005 to 0.10%, Cr: 0.40~3.00%, Ti: 0.010-0.50%, Ni: 0.01 to 0.50%, P: 0.050% or less, S: 0.0005~0.050%, N: 0.0015~0.0100%, O: 0.0035% or less, The balance is Fe and impurities. The following formula (i) is satisfied: The steel material contains MnS and MnTi composite sulfides, and the number density of MnS with a maximum length of 2.0 μm or more is 50.0 / mm 2 and the ratio of the number density of MnTi composite sulfides having a maximum length of 2.0 μm or more to the number density of MnS having a maximum length of 2.0 μm or more is 0.10 or more. Steel material. 3.6<(Si+Al+Ca) / Ti<27.0 (i) In the above formula, the element symbols represent the content (mass%) of each element contained in the steel material, and 0 is substituted if the element is not contained.
[0009] (2) The chemical composition contains, in mass%, a part of the Fe replaced by Mo: 0.10% or less W: 0.10% or less, Sn: 0.30% or less, Sb: 0.30% or less, As: 0.30% or less, Co: 0.30% or less, and Bi: 0.30% or less, It contains one or more selected from The steel material described in (1) above.
[0010] (3) The chemical composition contains, in mass%, a part of the Fe replaced by Nb: 0.10% or less, V: 0.10% or less, Ta: 0.050% or less, and B: 0.010% or less, It contains one or more selected from The steel material according to (1) or (2) above.
[0011] (4) The chemical composition contains, in mass%, a part of the Fe replaced by Ca: 0.010% or less, Mg: 0.010% or less, and REM: 0.010% or less, It contains one or more selected from The steel material according to any one of (1) to (3) above. Effect of the Invention
[0012] According to the present invention, it is possible to provide a steel material having excellent corrosion resistance in a high-temperature and high-concentration sulfuric acid corrosive environment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] In order to achieve the above object, the present inventors have conducted detailed investigations into the corrosion resistance of steel materials, and have come to the following findings.
[0014] Mn is an essential element for ensuring the strength and toughness of steel, but on the other hand, it forms MnS, which deteriorates the corrosion resistance in an acid corrosion environment. In the present invention, S has the effect of improving the corrosion resistance when contained together with Cu, so an extreme reduction in the amount of MnS is not preferable. In order to solve this problem, the relationship between MnS and corrosion resistance was studied in detail. As a result, it was found that MnTi composite sulfides containing Ti and Mn are less likely to become the starting point of corrosion than MnS.
[0015] Further investigation into methods for producing MnTi composite sulfides revealed that once Ti forms an oxide, it becomes difficult to incorporate Ti into MnS. Therefore, it was discovered that by appropriately incorporating elements such as Si, which are more easily oxidized than Ti, into the steel and consuming O in the steel through the formation of oxides of Si, etc., it is possible to suppress the formation of Ti oxides and incorporate Ti into MnS.
[0016] Furthermore, it was found that MnS can also be rendered harmless by reducing its size.
[0017] The present invention has been made based on the above findings. Each of the features of the present invention will be described in detail below.
[0018] (A) Chemical composition The reasons for limiting the content of each element are as follows. In the following description, "%" for the content means "mass %."
[0019] C: 0.010-0.20% C is an element that improves the strength of steel. However, if C is contained in excess, carbides increase and corrosion resistance deteriorates. Therefore, the C content is set to 0.010 to 0.20%. When strength is required, the C content is preferably 0.050% or more. Moreover, the C content is preferably 0.15% or less, and more preferably 0.10% or less.
[0020] Silicon: 0.04 to 1.00% Silicon is an element that contributes to deoxidation and strength improvement, and controls the form of oxides. However, if silicon is contained in excess, the amount of oxides increases, and corrosion resistance is impaired. Therefore, the silicon content is set to 0.04 to 1.00%. The silicon content is preferably 0.10% or more, and more preferably 0.20% or more. The silicon content is preferably 0.70% or less, and more preferably 0.60% or less.
[0021] Mn: 0.20~2.00% Mn is an element that improves strength. However, if Mn is contained in excess, coarse MnS is generated, and corrosion resistance and mechanical properties deteriorate. Therefore, the Mn content is set to 0.20 to 2.00%. The Mn content is preferably 0.50% or more, and more preferably 0.60% or more. In addition, the Mn content is preferably 1.70% or less, more preferably 1.50% or less, and even more preferably 1.30% or less.
[0022] Cu: 0.10-1.00% Cu is an element that exhibits significant corrosion resistance against sulfuric acid. However, if Cu is contained in excess, hot workability decreases, impairing productivity. Therefore, the Cu content is set to 0.10 to 1.00%. The Cu content is preferably 0.15% or more, 0.20% or more, or 0.25% or more. The Cu content is preferably 0.85% or less, and more preferably 0.70% or less.
[0023] Al: 0.005 to 0.10% Al is added as a deoxidizer. However, if an excessive amount of Al is contained, the corrosion resistance is impaired due to an increase in inclusions. Therefore, the Al content is set to 0.005 to 0.10%. The Al content is preferably 0.010% or more. Moreover, the Al content is preferably 0.07% or less.
[0024] Cr: 0.40~3.00% Cr is an element that has the effect of increasing hardenability and improving strength, as well as improving sulfuric acid resistance. However, when Cr is contained in excess, it forms oxides that tend to become corrosion initiation sites on the steel surface. Therefore, the Cr content is set to 0.40 to 3.00%. The Cr content is preferably 0.50% or more, more preferably 0.60% or more, and even more preferably 0.65% or more. In addition, the Cr content is preferably 2.50% or less.
[0025] Ti: 0.010~0.50% Ti is an element that forms nitrides and contributes to refining crystal grains and improving strength. However, if Ti is contained in excess, the increase in nitrides that cause corrosion impairs corrosion resistance. Therefore, the Ti content is set to 0.010 to 0.50%. The Ti content is preferably 0.013% or more, more preferably 0.015% or more, and even more preferably 0.020% or more. In addition, the Ti content is preferably 0.40% or less, and more preferably 0.30% or less.
[0026] Ni: 0.01 to 0.50% Ni is an element that improves corrosion resistance in an acid corrosion environment, and also has the effect of improving manufacturability in steel containing Cu. Cu has a large effect of improving corrosion resistance, but it is easily segregated, and if it is contained alone, it may promote cracking after casting. On the other hand, Ni has the effect of reducing the surface segregation of Cu. By containing Ni, in addition to suppressing Cu segregation and cast cracking, the occurrence of local corrosion due to segregation is also suppressed, so that the effect of improving corrosion resistance is obtained. However, Ni is an expensive element, and the inclusion of a large amount leads to an increase in steelmaking costs. Therefore, the Ni content is set to 0.01 to 0.50%. The Ni content is preferably 0.03% or more, more preferably 0.05% or more, and even more preferably 0.08% or more. In addition, the Ni content is preferably 0.40% or less, less than 0.29%, 0.25% or less, 0.20% or less, and more preferably 0.15% or less.
[0027] P:0.050% or less P is an impurity that reduces the mechanical properties and productivity of steel. Therefore, the upper limit of the P content is set to 0.050% or less. The P content is preferably 0.030% or less, and more preferably 0.025% or less. It is preferable to reduce the P content as much as possible, that is, the content may be 0%, but an extreme reduction leads to an increase in steelmaking costs. Therefore, the P content may be 0.001% or more.
[0028] S: 0.0005~0.050% S is generally an impurity that reduces the mechanical properties and productivity of steel materials. However, in the present invention, S has the effect of improving corrosion resistance in an acid corrosion environment when contained simultaneously with Cu. Therefore, the S content is set to 0.0005 to 0.050%. The S content is preferably 0.0010% or more, 0.0050% or more, or 0.0100% or more. In addition, the S content is preferably 0.040% or less, and more preferably 0.030% or less.
[0029] N: 0.0015~0.0100% N forms fine nitrides and contributes to improving the mechanical properties of steel materials. However, if N is contained in excess, it reduces the mechanical properties and productivity of steel materials. Therefore, the N content is set to 0.0015 to 0.0100%. The N content is preferably 0.0020% or more, and more preferably 0.0030% or more. In addition, the N content is preferably 0.0090% or less, and more preferably 0.0080% or less.
[0030] O: 0.0035% or less O is an impurity that forms coarse oxides that become the starting point of corrosion in an acid corrosion environment. Therefore, an upper limit is set for the O content, making it 0.0035% or less. The O content is preferably 0.0030% or less, and more preferably 0.0025% or less. It is preferable to reduce the O content as much as possible, that is, the content may be 0%, but an extreme reduction leads to an increase in steelmaking costs. Therefore, the O content may be 0.0013% or more, or 0.0020% or more.
[0031] In the chemical composition of the steel of the present invention, in addition to the above elements, one or more elements selected from Mo, W, Sn, Sb, As, Co, and Bi may be contained within the ranges shown below in order to further improve corrosion resistance. Note that these elements are not necessarily essential for steel materials, so the lower limit of the content is 0%. The reasons for limiting each element will be explained.
[0032] Mo: 0.10% or less Mo is an element that improves corrosion resistance in an acidic environment when contained together with Cu and Cr, and may be contained as necessary. However, since Mo is an expensive element, excessive inclusion leads to a decrease in economic efficiency. Therefore, the Mo content is set to 0.10% or less. The Mo content is preferably 0.09% or less, and more preferably 0.08% or less. In order to more reliably obtain the above effects, the Mo content is preferably 0.01% or more, more preferably 0.02% or more, and even more preferably 0.03% or more.
[0033] W: 0.10% or less W, like Mo, is an element that improves corrosion resistance in an acidic environment when contained together with Cu and Cr, so it may be contained as necessary. However, since W is also an expensive element, excessive inclusion leads to a decrease in economic efficiency. Therefore, the W content is set to 0.10% or less. The W content is preferably 0.09% or less, and more preferably 0.08% or less. In order to more reliably obtain the above effects, the W content is preferably 0.01% or more, more preferably 0.02% or more, and even more preferably 0.03% or more.
[0034] Sn: 0.30% or less Sn is an element that improves corrosion resistance in an acid corrosion environment when contained simultaneously with Cu, so it may be contained as necessary. However, if Sn is contained in excess, hot workability decreases. Therefore, the Sn content is set to 0.30% or less. The Sn content is preferably 0.25% or less, more preferably 0.20% or less, and even more preferably 0.15% or less. In order to obtain the above effects more reliably, the Sn content is preferably 0.01% or more, more preferably 0.02% or more, and even more preferably 0.05% or more.
[0035] Sb: 0.30% or less Sb is an element that improves corrosion resistance against sulfuric acid when contained simultaneously with Cu, so it may be contained as necessary. However, if Sb is contained in excess, hot workability decreases and productivity is impaired. Therefore, the Sb content is set to 0.30% or less. The Sb content is preferably 0.25% or less, more preferably 0.20% or less, and even more preferably 0.15% or less. In order to obtain the above effects more reliably, the Sb content is preferably 0.01% or more, more preferably 0.02% or more, and even more preferably 0.05% or more.
[0036] As: 0.30% or less Although As does not have a significant effect compared to Sb and Sn, it is an effective element for improving corrosion resistance in an acid corrosion environment, so it may be contained as necessary. However, if As is contained in excess, hot workability decreases. Therefore, the As content is set to 0.30% or less. The As content is preferably 0.20% or less, and more preferably 0.10% or less. In order to obtain the above effects more reliably, the As content is preferably 0.01% or more, more preferably 0.02% or more, and even more preferably 0.05% or more.
[0037] Co:0.30% or less Although Co does not have a significant effect compared to Sb and Sn, it is an element that improves corrosion resistance in an acid corrosion environment, so it may be contained as necessary. However, if Co is contained in excess, the economic efficiency decreases. Therefore, the Co content is set to 0.30% or less. The Co content is preferably 0.20% or less, and more preferably 0.10% or less. In order to obtain the above effects more reliably, the Co content is preferably 0.01% or more, more preferably 0.02% or more, and even more preferably 0.05% or more.
[0038] Bi:0.30% or less Although Bi does not have a significant effect compared to Sb and Sn, it is an element that improves corrosion resistance in an acidic environment, so it may be contained as necessary. However, if Bi is contained in excess, hot workability decreases. Therefore, the Bi content is set to 0.30% or less. The Bi content is preferably 0.20% or less, and more preferably 0.10% or less. In order to obtain the above effects more reliably, the Bi content is preferably 0.001% or more, more preferably 0.002% or more, and even more preferably 0.005% or more.
[0039] In the chemical composition of the steel of the present invention, in addition to the above elements, one or more elements selected from Nb, V, Ta, and B may be further contained within the ranges shown below in order to improve mechanical properties, etc. Note that these elements are not necessarily essential for steel materials, so the lower limit of the content is 0%. The reasons for limiting each element will be explained below.
[0040] Nb: 0.10% or less Nb, like Ti, is an element that forms nitrides and contributes to the refinement of crystal grains and the improvement of strength, so it may be contained as necessary. However, if Nb is contained in excess, the nitrides become coarse and the mechanical properties deteriorate. Therefore, the Nb content is set to 0.10% or less. The Nb content is preferably 0.09% or less, more preferably 0.08% or less, and even more preferably 0.07% or less. In order to obtain the above effects more reliably, the Nb content is preferably 0.005% or more, more preferably 0.010% or more, and even more preferably 0.015% or more.
[0041] V:0.10% or less V, like Ti and Nb, is an element that forms nitrides and contributes to refining crystal grains and improving strength, so it may be contained as necessary. However, if V is contained in excess, the nitrides become coarse and mechanical properties deteriorate. Therefore, the V content is set to 0.10% or less. The V content is preferably 0.08% or less, more preferably 0.06% or less, and even more preferably 0.04% or less. In order to obtain the above effects more reliably, the V content is preferably 0.005% or more.
[0042] Ta: 0.050% or less Ta is an element that contributes to improving strength, and also contributes to improving corrosion resistance, although the mechanism is not necessarily clear, so it may be contained as necessary. However, Ta is an expensive element, and the inclusion of a large amount of Ta increases the steelmaking cost. Therefore, the Ta content is set to 0.050% or less. The Ta content is preferably 0.040% or less, more preferably 0.030% or less, and even more preferably 0.020% or less. In order to obtain the above effects more reliably, the Ta content is preferably 0.001% or more, and more preferably 0.005% or more.
[0043] B: 0.010% or less Since B is an element that improves hardenability and increases strength, it may be contained as necessary. However, even if B is contained in excess, the effect is saturated and the toughness of the base material and HAZ may decrease. Therefore, the B content is set to 0.010% or less. The B content is preferably 0.008% or less, more preferably 0.006% or less, and even more preferably 0.004% or less. In order to obtain the above effects more reliably, the B content is preferably 0.0003% or more, and more preferably 0.0005% or more.
[0044] In the chemical composition of the steel of the present invention, in addition to the above elements, one or more elements selected from Ca, Mg, and REM may be further contained within the ranges shown below for the purpose of deoxidization and inclusion control. Note that these elements are not necessarily essential in steel materials, so the lower limit of the content is 0%. The reasons for limiting each element will be explained.
[0045] Ca: 0.010% or less Ca is an element mainly used to control the morphology of sulfides, and may be included as necessary to form fine oxides. However, if Ca is included in excess, mechanical properties may be impaired. Therefore, the Ca content is set to 0.010% or less. The Ca content is preferably 0.005% or less. In order to more reliably obtain the above effects, the Ca content is preferably 0.0005% or more, more preferably 0.0010% or more, and even more preferably 0.0020% or more.
[0046] Mg: 0.010% or less Mg may be added as necessary to form fine oxides. However, excessive addition of Mg increases the steelmaking cost. Therefore, the Mg content is set to 0.010% or less. The Mg content is preferably 0.005% or less, and more preferably 0.003% or less. In order to more reliably obtain the above effects, the Mg content is preferably 0.0001% or more, more preferably 0.0003% or more, and even more preferably 0.0005% or more.
[0047] REM: 0.010% or less REM (rare earth elements) are elements mainly used for deoxidation, and may be included as necessary to form fine oxides. However, excessive addition of REM leads to increased steelmaking costs. Therefore, the REM content is set to 0.010% or less. The REM content is preferably 0.005% or less, and more preferably 0.003% or less. In order to more reliably obtain the above effects, the REM content is preferably 0.0001% or more, more preferably 0.0003% or more, and even more preferably 0.0005% or more.
[0048] Here, REM is a general term for Sc, Y, and lanthanoids, a total of 17 elements, and the REM content means the total amount of the above elements. Note that lanthanoids are industrially added in the form of misch metals.
[0049] In the chemical composition of the steel material of the present invention, the balance is Fe and impurities. Here, the impurities refer to components that are mixed in due to raw materials such as ores and scraps or other factors during industrial production of the steel material, and are permissible within a range that does not adversely affect the steel material of the present invention.
[0050] 3.6<(Si+Al+Ca) / Ti<27.0 (i) As described above, when Ti becomes an oxide, it becomes difficult to form MnTi composite sulfides. However, it is industrially difficult to reduce the O content extremely, and it is difficult to suppress the formation of oxides. Therefore, in order to suppress the generation of Ti oxides, it is effective to increase the total content of Si, Al, and Ca, which are more likely to become oxides than Ti, relative to the Ti content. As a result, O in the steel is consumed, and Ti does not form an oxide but is contained in MnS, so that MnTi composite sulfides are formed and the corrosion resistance is improved. On the other hand, if the total content of Si, Al, and Ca becomes excessive relative to the Ti content, not only the effect of improving the corrosion resistance is saturated, but also coarse oxides that become the starting point of corrosion are formed, so that the corrosion resistance is rather reduced. Therefore, it is necessary to satisfy formula (i). However, the element symbols in formula (i) represent the content (mass%) of each element contained in the steel, and 0 is substituted if it is not contained.
[0051] The value in formula (i) is preferably 4.0 or more, and more preferably 6.0 or more, and the value in formula (i) is preferably 25.0 or less, and more preferably 20.0 or less.
[0052] (B) Inclusions The steel material according to the present invention contains MnS and MnTi complex sulfides in the steel material. The number density of MnS having a maximum length of 2.0 μm or more is 50.0 / mm 2 In addition, the ratio of the number density of MnTi composite sulfides having a maximum length of 2.0 μm or more to the number density of MnS having a maximum length of 2.0 μm or more is 0.10 or more.
[0053] In addition, since MnS having a maximum length of less than 2.0 μm has almost no effect on the corrosion resistance of steel materials, the present invention targets inclusions having a maximum length of 2.0 μm or more. In the following description, MnS having a maximum length of 2.0 μm or more will be simply referred to as MnS, and MnTi composite sulfides having a maximum length of 2.0 μm or more will also be simply referred to as MnTi composite sulfides.
[0054] As described above, in the steel material of the present invention, the formation of MnS is unavoidable. However, MnS acts as a starting point for corrosion and deteriorates the corrosion resistance in an acid corrosion environment. Therefore, the number density of MnS is set to 50.0 / mm 2 The number density of MnS is less than 45.0 / mm 2 It is preferable that the thickness is 40.0 / mm or less. 2 More preferably, it is:
[0055] On the other hand, in the steel material of the present invention, an extreme reduction in the content of Mn and S is not preferable from the viewpoint of improving the strength and corrosion resistance. In order to achieve both, it is necessary to render MnS harmless. When MnTi composite sulfides are formed, MnS is rendered harmless and is less likely to become a starting point of corrosion. Although the detailed reason why the corrosion resistance is improved by the formation of MnTi composite sulfides is unclear, it is considered that MnS is easily dissolved in sulfuric acid and becomes a starting point of corrosion, while MnTi composite sulfides have a lower solubility than MnS and are less likely to become a starting point of corrosion.
[0056] For the above reasons, in the present invention, the ratio of the number density of MnTi composite sulfides to the number density of MnS is set to 0.10 or more, preferably 0.12 or more, and more preferably 0.15 or more.
[0057] The number density of MnS and the number density of MnTi composite sulfides are measured by energy dispersive X-ray analysis (EDS) equipped in a scanning electron microscope (SEM). The measurement magnification is 1000 times, and the maximum length of MnS and MnTi composite sulfides detected in the field of view is measured. Then, the number of inclusions with a maximum length of 2.0 μm or more is counted and divided by the field of view area to obtain the number density and the number density ratio.
[0058] Inclusions are identified by EDS, and inclusions with a total content of Mn and S of 90% by mass or more are determined to be MnS, and inclusions in which a Ti peak is detected, the Ti content is 12% or more, and the total content of Mn, S, and Ti is 90% by mass or more are determined to be MnTi composite sulfides. When MnS contains 12% or more Ti and becomes an MnTi composite sulfide, MnS is significantly rendered harmless.
[0059] (C) Plate thickness The thickness of the steel material according to the present invention is not particularly limited, but is preferably 0.6 to 25.0 mm, and more preferably 1.0 to 20.0 mm.
[0060] (D) Yield stress The yield stress of the steel material according to the present invention is not particularly specified, but is preferably 300 MPa or more at 25°C, and more preferably 310 MPa or more.
[0061] (E) Manufacturing method A method for producing a steel material according to an embodiment of the present invention will be described. The steel material according to this embodiment includes steel plates, steel sections, steel pipes, etc., which are produced by hot rolling and, if necessary, cold rolling.
[0062] The steel material according to the present embodiment is manufactured by melting steel in a conventional manner, adjusting the components, casting the resulting steel billet, hot rolling the resulting steel billet, and further performing cold rolling as necessary. The heating temperature before hot rolling is preferably 1220 to 1400°C. In this temperature range, MnTi composite sulfides are formed. Although the detailed mechanism is not clear, it is believed that Ti precipitates as TiS in this temperature range. It is believed that MnTi composite sulfides are formed by precipitating MnS with the precipitated TiS as a nucleus.
[0063] If the heating temperature before hot rolling exceeds 1400°C, energy is wasted and the manufacturing cost increases. On the other hand, if the heating temperature before hot rolling is set to 1220°C or higher, TiS, which serves as nuclei, is sufficiently precipitated, and as a result, the ratio of the number density of MnTi composite sulfides to the number density of MnS can be set to 0.10 or more.
[0064] The holding time in the above temperature range is preferably 60 to 150 minutes. By holding the above temperature range for 60 minutes or more, TiS and MnS can be sufficiently precipitated, and the ratio of the number density of MnTi composite sulfides to the number density of MnS can be set to 0.10 or more. On the other hand, by holding the above temperature range for 150 minutes or less, coarsening of MnS that does not form MnTi composite sulfides can be suppressed.
[0065] After hot rolling, the hot-rolled steel sheet is subjected to the next process such as coiling. During this process, the temperature of the steel sheet drops, but it is desirable that the time from the completion of hot rolling until the temperature reaches 400°C is 4 hours or more. Exposure to this temperature range promotes the formation of MnTi composite sulfides with TiS as the nucleus. After hot rolling, the steel sheet may be cold-rolled to obtain a cold-rolled steel sheet. Furthermore, heat treatment may be performed after cold rolling.
[0066] When producing a steel pipe from the obtained steel plate, the steel plate may be formed into a tubular shape and welded, and for example, a UO steel pipe, an electric resistance welded steel pipe, a forge welded steel pipe, a spiral steel pipe, etc. may be produced.
[0067] The present invention will be described in more detail below with reference to examples. Note that the conditions in the examples shown below are examples of conditions adopted to confirm the feasibility and effects of the present invention, and the present invention is not limited to these examples. In addition, various conditions may be adopted in the present invention as long as they do not deviate from the gist of the present invention and achieve the object of the present invention. EXAMPLES
[0068] Steels (A to AB) having the chemical compositions shown in Table 1 were melted and the steel ingots were hot rolled under the conditions shown in Table 2 to produce hot-rolled steel sheets with a thickness of 20 mm. Some of the steel sheets were cooled after hot rolling to simulate coiling, and then further cold-rolled to produce cold-rolled steel sheets with a thickness of 13 mm.
[0069] [Table 1]
[0070] [Table 2]
[0071] Test pieces for SEM observation were cut out from each steel plate obtained, and the number density of inclusions was measured using the EDS equipped in the SEM. The measurement magnification was 1000 times, and the maximum length of MnS and MnTi composite sulfides detected in the field of view was measured, and the number of inclusions with a maximum length of 2.0 μm or more was counted and divided by the field of view area to obtain the number density and the number density ratio.
[0072] Furthermore, the obtained steel sheets were subjected to various performance evaluation tests as described below.
[0073] <Sulfuric acid resistance> A test piece with a thickness of 1 mm, width of 25 mm, and length of 25 mm was taken from the center of each steel plate and finished with wet polishing with #400 to prepare a test piece for evaluating corrosion resistance. The corrosion resistance was evaluated by a sulfuric acid immersion test in which the test piece was immersed in a 75% sulfuric acid aqueous solution at 125°C for 6 hours.
[0074] Then, the corrosion rate was calculated from the corrosion weight loss of the test piece in the sulfuric acid immersion test. In this example, the corrosion rate in the sulfuric acid immersion test was 10.0 mg / cm 2 / h or less, it was determined that the sulfuric acid resistance was excellent.
[0075] <Yield stress> Tensile test pieces with a thickness of 1 mm were prepared and subjected to tensile tests to determine the yield stress in accordance with JIS Z 2241:2011. Those with a yield stress of 300 MPa or more were judged to have excellent yield stress.
[0076] Table 3 shows the measurement results of the number density of inclusions, as well as the evaluation results of the sulfuric acid immersion test and the tensile test.
[0077] [Table 3]
[0078] As shown in Table 3, Test Nos. 1 to 24, which satisfy all the provisions of the present invention, showed excellent results in all performance evaluation tests. In contrast, Test Nos. 25 to 33, which are comparative examples, showed poor results in at least one of sulfuric acid resistance and yield stress. [Industrial Applicability]
[0079] The steel material of the present invention can be used in smoke exhaust systems for boilers that burn fossil fuels such as heavy oil and coal, gas fuels such as liquefied natural gas, general waste such as municipal waste, industrial waste such as waste oil, plastics, and used tires, and sewage sludge, etc. Specifically, it can be suitably used in air preheaters for boilers, etc.
Claims
1. The chemical composition, in mass%, is C: 0.010-0.20%, Si: 0.04-1.00%, Mn: 0.20-2.00%, Cu: 0.10-1.00%, Al: 0.005-0.10%, Cr: 0.40-3.00%, Ti: 0.010-0.50%, Ni: 0.01-0.50%, P: 0.050% or less, S: 0.0005-0.050%, N: 0.0015-0.0100%, O: 0.0035% or less, The balance is Fe and impurities. The following formula (i) is satisfied: The steel material contains MnS and MnTi composite sulfides, and the number density of MnS with a maximum length of 2.0 μm or more is 50.0 / mm 2 and the ratio of the number density of MnTi composite sulfides having a maximum length of 2.0 μm or more to the number density of MnS having a maximum length of 2.0 μm or more is 0.10 or more. Steel material. 3.6<(Si+Al+Ca) / Ti<27.0...(i) In the above formula, the element symbols represent the content (mass%) of each element contained in the steel material, and 0 is substituted when the element is not contained.
2. The chemical composition is, in mass %, replacing a part of the Fe, Mo: 0.10% or less, W: 0.10% or less, Sn: 0.30% or less, Sb: 0.30% or less, As: 0.30% or less, Co: 0.30% or less, and Bi: 0.30% or less, It contains one or more selected from The steel material according to claim 1.
3. The chemical composition is, in mass %, replacing a part of the Fe, Nb: 0.10% or less, V: 0.10% or less, Ta: 0.050% or less, and B: 0.010% or less, It contains one or more selected from The steel material according to claim 1 or 2.
4. The chemical composition is, in mass %, replacing a part of the Fe, Ca: 0.010% or less, Mg: 0.010% or less, and REM: 0.010% or less, It contains one or more selected from The steel material according to any one of claims 1 to 3.
Citation Information
Patent Citations
High workability and good weldability sulfuric acid dew point corrosion resistant steel sheet
JP2001164335A
Low alloy steel having excellent hydrochloric acid- corrosion and sulfuric acid-corrosion resistance and welded joint thereof
JP2003213367A
Acid corrosion resistant steel
JP2007239094A
Acid dew-point corrosion resistant steel and exhausted gas flow path structure member
JP2012057221A
steel
JP2020111790A